Front Cover: Catalytic Transfer Hydrogenation of Lignocellulosic Biomass Model Compounds Furfural and Vanillin with Ethanol by an Air‐stable Iron(II) Complex (ChemCatChem 3/2023). Issue 3 (8th February 2023) - Ghosh, Rahul; Behera, Rakesh R.; Panda, Surajit; Behera, Sandeep K.; Jana, Narayan Ch.; Bagh, Bidraha
Abstract : The Front Cover displays transfer hydrogenation as a bridge between biomass and a bio‐refinery. Biomass is considered as a sustainable alternative to petroleum‐based resources and the effective use of biomass feedstock presents a crucial opportunity. For the sustainable development of biofuel and fine chemicals, lignocellulosic biomass may be established as one of the most promising carbon feedstocks. Therefore, the importance of bio‐refineries is growing significantly in the present era. Each year bio‐refineries are producing a huge amount of furfural and vanillin which are the source of important fine chemicals furfuryl alcohol and vanillyl alcohol, respectively, with wide applications. It is important to develop catalytic process such as catalytic transfer hydrogenation to reduce furfural and vanillin to furfuryl alcohol and vanillyl alcohol, respectively. In their Research Article, B. Bagh and co‐workers have developed a base metal iron catalyst which proved to be a very effective catalyst for the transfer hydrogenation of biomass‐model compounds furfural and vanillin to furfuryl alcohol and vanillyl alcohol, respectively. More information can be found in the Research Article by B. Bagh and co‐workers .